Smart University: A Premise for Regional Development. Evidence from South-East Region of Romania - G. Marchis (European Alliance for Innovation (EAI), 2021)
INTRODUCTION: A Smart University is a creative environment with a high level of adaptive capacity building to current societies' challenges. From regional development planning perspective, a Smart University proves an anticipatory rather than reactionary adaptation to the context conditions, providing more development alternatives into the future, assuring in this way the regional performance and competitiveness.OBJECTIVES: The paper tackles 3 important perspectives of the role of HEIs from South-East region of Romania to regional development: The University as an Education and Training Platform, The University as a Research Platform and The University as a Knowledge and Technology Transfer Platform. An interesting research question becomes whether and to what extent the academia can contribute to territorial development policies in South-East region of Romania?METHODS: This research-paper highlights the main characteristics of the academic environment of South-East region analysing at intra-regional level, the educational offer and the results of HEIs activities in the fields of research and knowledge transfer.RESULTS: A Smart University should first and foremost help the local community to develop their territorial capital, which is defined by OCDE as "an ensemble of geographical (accessibility, agglomeration economies, natural resources), economic (factor endowments, competences), cognitive (knowledge, human capital, cooperation networks), social (solidarity, trust, associations), and cultural assets ("understandings, customs and informal rules that enable economic agents to work together under conditions of uncertainty").CONCLUSION: Rethinking higher education system is the first step in boosting regional development in the digital age.